Chanted narratives: the living "katha-vachana" tradition - Kaushal, Molly (Indira Gandhi National Centre for the Arts D.K. Printworld, 2001)
Contributed articles presented at workshop
Includes bibliographical references
Keywords: Konferenzschrift; Konferenzschrift -- 1997 -- Delhi; Sprechgesang; Mündliche Überlieferung; Indien; Aufsatzsammlung; Mündliche Literatur; Epik